2021
DOI: 10.3390/molecules26092748
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Swertiamarin against Methylglyoxal-Induced Epithelial-Mesenchymal Transition by Improving Oxidative Stress in Rat Kidney Epithelial (NRK-52E) Cells

Abstract: Increased blood glucose in diabetic individuals results in the formation of advanced glycation end products (AGEs), causing various adverse effects on kidney cells, thereby leading to diabetic nephropathy (DN). In this study, the antiglycative potential of Swertiamarin (SM) isolated from the methanolic extract of E. littorale was explored. The effect of SM on protein glycation was studied by incubating bovine serum albumin with fructose at 60 °C in the presence and absence of different concentrations of swerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that swertiamarin not only downregulates the expression of hyperglycemia‐induced advanced glycation end products (AGEs) in the serum and renal tissue but also prevents renal fibrosis by inhibiting epithelial–mesenchymal transition in renal tissues. The silico analysis indicates that swertiamarin inhibits the binding of various AGEs to the recombinant receptor for AGEs (RAGE), thereby inhibiting the AGE‐RAGE axis (Parwani, Patel, Bhagwat, et al, 2021; Parwani, Patel, Patel, & Mandal, 2021). In addition, Sonawane et al found considerable improvement in the histology of glomerular function in swertiamarin (50 mg/kg, ig)‐treated animals receiving an aqueous extract of E. littorale , suggesting the significant kidney‐protective effect of swertiamarin (Sonawane et al, 2010).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…It has been reported that swertiamarin not only downregulates the expression of hyperglycemia‐induced advanced glycation end products (AGEs) in the serum and renal tissue but also prevents renal fibrosis by inhibiting epithelial–mesenchymal transition in renal tissues. The silico analysis indicates that swertiamarin inhibits the binding of various AGEs to the recombinant receptor for AGEs (RAGE), thereby inhibiting the AGE‐RAGE axis (Parwani, Patel, Bhagwat, et al, 2021; Parwani, Patel, Patel, & Mandal, 2021). In addition, Sonawane et al found considerable improvement in the histology of glomerular function in swertiamarin (50 mg/kg, ig)‐treated animals receiving an aqueous extract of E. littorale , suggesting the significant kidney‐protective effect of swertiamarin (Sonawane et al, 2010).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…1,2 ARPs are considered potential substitutes for Maillard reaction products (MRPs) 3 to produce expected flavor and avoid the loss of desirable volatile components of MRPs 4 during the thermal processing of food due to their relatively stable physicochemical properties. 5,6 The type of amino acids and reducing sugars could affect the components of their ARPs and MRPs. 7 Lysine (Lys) is a basic amino acid containing two active sites of −NH 2 (α-and ε-NH 2 ), 8 both of which are highly reactive to interact with reducing sugars to form different Lys-ARPs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Amadori rearrangement products (ARPs) are generated at the initial stage of the Maillard reaction. , ARPs are considered potential substitutes for Maillard reaction products (MRPs) to produce expected flavor and avoid the loss of desirable volatile components of MRPs during the thermal processing of food due to their relatively stable physicochemical properties. , …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that sodium oleate has damage to the kidneys [8]. NRK-52e is the rat proximal tubular epithelial cell, which is often used to study kidney disease [9]. Therefore, this study used sodium oleate to stimulate NRK-52e cells to explore whether it could induce lipid deposition in NRK-52e cells.…”
Section: Introductionmentioning
confidence: 99%